Answer:
B. f(x) = (1/2)(x -6)^2 +3/2
Explanation:
Let's do this in general terms for a focus at (h, k) and a directrix at y = d.
We start with a generic point (x, y) and we want to have it satisfy the relation that its distance from the focus is the same as its distance from the directrix (the definition of a parabola).
... distance from (x, y) to the focus = √((x -h)^2 +(y -k)^2)
... distance from (x, y) to the directrix = √((y - d)^2)
Equating these distances and squaring both sides of the equation, we get ...
... √((x -h)^2 +(y -k)^2) = √((y - d)^2)
... (x -h)^2 +(y -k)^2 = (y -d)^2
Expanding the y term, we find we can cancel the y^2 terms to get an equation you're more familiar with.
... (x -h)^2 +y^2 -2ky +k^2 = y^2 -2dy +d^2
... (x -h)^2 +k^2 -d^2 = 2y(k -d) . . . . . . note the difference of squares on the left
Dividing by the coefficient of y gives ...
... y = 1/(2(k-d))·(x -h)^2 +(k+d)/2 . . . . . . equation of a general parabola (opens vertically)
___
Sometimes, you will see the difference (k-d) designated as 2p, so the equation is written
... y = 1/(4p)·(x -h)^2 + (k-p) . . . . . p is the distance from focus (h, k) to vertex
And sometimes, (h, k) is defined as the vertex, not the focus, so the equation is written
... y = 1/(4p)·(x -h)^2 +k . . . . . . . (h, k) is the vertex
_____
For focus (6, 2) and directrix y=1, we have (h, k) = (6, 2) and d=1. Using the first bold equation above, our equation for the parabola is ...
... y = 1/(2(2-1))·(x -6)^2 +(2+1)/2
... y = (1/2)(x -6)^2 +3/2 . . . . matches selection B